2010
DOI: 10.1007/s11604-009-0379-3
|View full text |Cite
|
Sign up to set email alerts
|

Innovative radiographic system to improve the sharpness of radiographs: could a phase-shift effect contribute to improved image-quality for plain computed radiographs for general use?

Abstract: This technique may be suitable for clinical use and may contribute to improved image-quality in general radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…5 We have previously shown that an image of the hand of a patient with rheumatoid arthritis was more clearly depicted when obtained on PCR than on conventional radiography because of the higher spatial resolution of the former. 6 The Talbot-Lau-type method, which is a phase-contrast technology, is normal for practical use. 14 This method does not need a special X-ray tube; however, it is essential to use special grating to obtain images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 We have previously shown that an image of the hand of a patient with rheumatoid arthritis was more clearly depicted when obtained on PCR than on conventional radiography because of the higher spatial resolution of the former. 6 The Talbot-Lau-type method, which is a phase-contrast technology, is normal for practical use. 14 This method does not need a special X-ray tube; however, it is essential to use special grating to obtain images.…”
Section: Discussionmentioning
confidence: 99%
“…4 Moreover, we and other investigators have previously demonstrated that phase-contrast images can depict hard tissues such as micro-calcification associated with breast cancer or trabeculae associated with the hand. [5][6][7] To our knowledge, whether this new method is useful for assessing mandibular third molars has not previously been examined.…”
Section: Introductionmentioning
confidence: 99%